Potret Identitas Religius Siswa SMA: Studi Komparatif Gender pada Peserta Didik Tingkat Pertama Kota Sungai Penuh: Studi Komparatif Gender pada Peserta Didik Tingkat Pertama Kota Sungai Penuh - Utami, Melda Putri; Yusuf, Muhamad; Damni, Albertos (The Magister of Islamic Education IAIN Pontianak, 2025)
This study aims to analyze the differences in religious identity among high school students based on gender in Sungai Penuh City. Religious identity is acrucial aspect in shaping students' character, encompassing dimensions of belief, religious practices, and moral values. The focus of this study is to describe how male and female students understand and practice religious values, as well as the factors influencing these differences. This research employs a quantitative approach with a random sampling technique. Data were collected through questionnaires distributed to first-year high school students. Data analysis was conducted to evaluate gender differences in terms of religiosity. The findings indicate that female students exhibit a higher level of religious identity compared to male students. This result reflects a greater involvement of females in religious practices, both in school and community-based activities. Social and cultural factors, such as gender roles in societal norms, significantly influence these differences. The implications of this study highlight the need for a more inclusive approach in religious education to address the needs of both male and female students. Additionally, this study contributes to the development of a religious education curriculum that is relevant to local contexts and gender differences.